Pengaruh kualitas informasi dan manfaat informasi terhadap kepuasan masyarakat pada instagram kantor imigrasi kelas 1 TPI denpasar - Bima Fatwa Ramadhan; Kadek Jemmy Waciko; Ni Putu Ritra Trees Ari Kartika Hadi Saraswati (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study aims to analyze the influence of information quality and information utility on public satisfaction regarding the Instagram account of the Class I TPI Denpasar Immigration Office. The study is motivated by the importance of social media as an effective public communication tool for conveying immigration service information to the public. A quantitative approach was employed, utilizing a survey method involving 100 respondents who had accessed the Class I TPI Denpasar Immigration Office's Instagram account. Data were collected via questionnaires and analyzed using multiple linear regression with the aid of IBM SPSS. The results indicate that both information quality and information utility have a positive and significant effect on public satisfaction, both individually and simultaneously. Furthermore, while both variables explain a substantial portion of the variation in public satisfaction regarding the information conveyed via Instagram, the information utility variable is far more dominant. These findings demonstrate that higher quality and utility of the information provided lead to higher levels of satisfaction among the public as information users. The study offers practical implications for the Class I TPI Denpasar Immigration Office to continuously enhance the quality and utility of information shared on social media, thereby supporting effective public communication and boosting public satisfaction